GAMBARAN TINGKAT DEPRESI PADA LANJUT USIA DI WILAYAH KERJA PUSKESMAS PARONGPONG - Jeanny Rantung (Jurnal Skolastik Keperawatan, 2019)
Elderly is a natural process that occurs in the stages of growth and development of each person. Getting older will experience decreased in physical, biological, social and psychological. Depression is one of the problems that can occur in the elderly due to psychomotor and cognitive decreased. This study aims to identify the level of depression in the elderly, using descriptive methods. The sample used was purposive sampling involving 48 elderly people in the working area of ​​the Parongpong Community Health Center. This study was using the Geriatric Depression Scale with 15 questions to measure the level of depression in the elderly. Data were analyzed using frequency distribution. The results showed that 30 elderly (62.5%) experience depression. Advice that can be given to nurses is to provide health promotion through counseling about the management and prevention of depression to the elderly and families. Keywords: elderly, depression, depression level